A MINI REVIEW ON THE MOLECULAR STRUCTURE, SPECTRAL CHARACTERISTICS, SOLVENT-FREE SYNTHESIS, AND MULTIDISCIPLINARY APPLICATIONS OF CYANINE DYES - Islam M. Abdellah, and Mohamed R. Eletmany, (Chelonian Research Foundation, 2023)
Cyanine dyes, a subclass of multifunctional organic compounds, have attracted considerable scientific attention owing to their distinctive molecular structures, exceptional spectral attributes, and diverse applications spanning various scientific domains. This comprehensive review elucidates the molecular architectures, electronic configurations, and spectral properties of cyanine dyes, underscoring their unique absorption and emission profiles that render them invaluable tools in the fields of medicine, pharmacology, and engineering. Despite possessing remarkable traits such as stability, high molar extinction coefficients, and heightened pH sensitivity, this dye class has received comparatively limited scrutiny and evaluation in recent decades. Consequently, this review concentrates on their structural and spectral attributes, which showcase their distinctive qualities. Moreover, the review delves into the manifold applications of cyanine dyes, along with their solvent-free synthesis facilitated by microwave irradiation as an efficient methodology for minimizing chemical waste and reaction time. These techniques enable environmentally sustainable synthesis practices, not only for novel product development but also for the eco-friendly synthesis of pre-existing chemicals, achieved through the complete elimination of solvent usage. Keywords: Cyanine Dyes, Spectral Behaviour, Classification, Microwave-assisted synthesis; Applications.